Linux For You (with CD & DVD) (Monthly): Vol.9 Issue.10 December'2011 - Monthly (EFY Enterpries Pvt. Ltd. New Delhi, 2011)
Subscription Period- 2011(Jan to Dec)
Keywords: Computer Science/ Information Science/ MCA/ M Tech CSE